PENGEMBANGAN ALAT EVALUASI PRODUK BOUSTE - Tati Rohaeti; Astuti Astuti (Universitas Pendidikan Indonesia, 2017)
This research assessing about the development of an evaluation tool bouste houder products .The purpose of this research to develop an evaluation tool products bouste houder formerly less arranged systematically of its , to make designs an evaluation tool , get the result validation by the matter and expert evaluation , and analyzes the results of validation as an assessment feasibility an evaluation tool .An evaluation tool bouste houder products in the form of the format of an assessment that will be prepared based on several indicators the assessment criteria assessment guidelines in the form of a register of checks .Research methodology used research methodology quantitative research with a model that is a method of research and development ( research and development / r amp; d ) through the stage the study of introduction , the development of an evaluation tool , and test the validity of the revision of the stage .Based on the results of validation shows that the development of an evaluation tool boust products. The results of validation experts inferred according to the scale presentation feasibility refer to data on obtained it can be said wortthy to used as a reference default or standard in judging study result students and a guide lecturer in assessing products bouste houder.